Analisis Perbandingan Prediksi Kebangkrutan Dengan Model Altman Z-Score, Model Springate, Model Zmijewski Dan Model Grover Pada Sektor Consumer Non-Cyclicals - Ponny Harsanti; Angela Almayda Aditya; Alfiyani Nur Hidayanti (CV. Ulil Albab Corp, 2024)
This research aims to determine the comparison of the Altman Z-Score, Springate, Zmijewski, and Grover models in predicting company bankruptcy in the non-cyclical consumer sector listed on the Indonesia Stock Exchange for the 2015 - 2021 period. To find out the most accurate model in predicting company bankruptcy in non-cyclical consumer sector listed on the Indonesia Stock Exchange for the 2015 - 2021 period. The sampling technique used purposive sampling so that 23 companies were used as research samples. This research uses non-parametric statistical data analysis, namely the Kruskal Wallis difference test and accuracy tests on bankruptcy prediction models. The test results of this research show that there are differences in predictions between the Altman Z-Score, Springate, Zmijewski, and Grover models in predicting company bankruptcy in the non-cyclical consumer sector listed on the Indonesia Stock Exchange for the 2015 - 2021 period. The Springate model is the most accurate prediction model with the accuracy rate reached 69.56%.